The Effect of Pranayama Yoga and Education on Anxiety and Fatigue in Hemodialysis Patients at X Hospital in West Java - Sriulina, Liana; Widani, Ni Luh; Priyo Hastono, Sutanto (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
Chronic renal failure patients on hemodialysis have physical and psychological changes that cause worry and fatigue. The study examines how pranayama yoga and education affect anxiety and exhaustion at X Hospital in West Java hemodialysis patients. A single group pre-post-test was used in the quasi-experimental investigation. From June 12 to July 12, 2023, 35 hemodialysis patients participated. These patients had nine yoga pranayama and education sessions. The study found that 85.7% of participants experienced low-level anxiety before and 100% after the intervention. The t-dependent test showed a significant difference in anxiety (p 0.001) and exhaustion (p=0.001) before and after the session. Even after controlling for age, gender, and hemodialysis time, pranayama yoga and education therapies significantly reduced anxiety in multivariate linear regression. The P-value for this influence is 0.009. Age (p-value=0.989), gender (p-value=0.212), and protracted haemodialytic treatments (p-value=0.525) do not affect nervousness—the effects of the intervention on anxiety and fatigue. Even after controlling for age, gender, and hemodialysis duration, pranayama yoga and education did not affect anxiety and fatigue. Additional research on sleep quality and hemoglobin levels is recommended.